Hooray for Amanda & her alligator! - Willems, Mo. (New York : Balzer + Bray, 2011)
Amanda and her alligator have lots of fun together, but when Amanda's grandfather buys her a panda, Alligator must learn to make new friends.
Pub Weekly
School Library Journal starred
Pub Weekly, March 2011
School Library Journal starred, May 2011
2.6
K-3
Keywords: Alligators -- Juvenile fiction; Friendship -- Juvenile fiction; Toys -- Juvenile fiction; Alligators -- Fiction; Friendship -- Fiction; Toys -- Fiction; Alligators -- Fiction; Friendship -- Fiction; Toys -- Fiction; Picture books for children